The Principle of Circular and Cumulative Causation: Myrdal, Kaldor and Contemporary Heterodox Political Economy - O'Hara, Phillip (Routledge, 2009)
The first main section studies the similarities and differences between the Myrdalian and Kaldorian CCC frameworks. The second section develops a general system model of integration between the two traditions. There is a large measure of continuity between the two CCC approaches; they complement each other. Myrdalian CCC concentrates on the social provisioning aspect of development, while Kaldorian CCC centres on demand-supply relationships linked to the manufacturing sector. Linking both CCC approaches in an integrative model enhances our understanding of development and growth dynamics, and contributes to the development of institutional-evolutionary political economy. The third section illustrates a contemporary application of CCC through an investigation of the dynamic forces expanding the scope, network interaction and conceptual-empirical edifice of heterodox political economy.